Wage Gap Analysis Between Gender in The Informal Sector During Covid-19 - Kafabih, Abdullah; Ridwan, Mohamad (Jurnal Ilmu Ekonomi Terapan, 2022)
The level of wages received by workers in the informal sector tends to be lower than workers in the formal sector. This condition can be exacerbated if there is gender discrimination, which causes differences in the distribution of wages for workers. This study aims to identify wage discrimination between genders of informal sector workers. The independent variables of this study consisted of education, age, training, incentives, gender, and type of work. Gender wage ratio and gender productivity ratio were estimated simultaneously using non-linear logistic regression method. This study found evidence of wage discrimination against women in the informal sector. Education and training contribute positively to equal pay between women and men